COMMUNICATION STRATEGY IN LIVE COMMERCE: A CASE STUDY OF SHOPEE LIVE FINNA FOOD BY CREVITI MEDIA AGENCY - Munir, Miftakhul; Mansoor, Alvanov Zpalanzani (DEKAVE : Jurnal Desain Komunikasi Visual, 2025)
Live commerce through the Shopee Live feature has emerged as an increasingly popular digital marketing strategy in Indonesia. However, few studies have specifically examined how communication strategies are constructed by creative agencies in live streaming sessions. This study aims to explore the verbal and visual communication strategies implemented by Creviti Media Agency in the execution of Shopee Live sessions for the Finna Food brand, using the AIDMA model and Marketing Mix framework. A qualitative descriptive case study method was employed, with data collected through interviews, participant observation, and documentation. The findings reveal that verbal communication strategies include interactivity, storytelling, and call-to-action. Meanwhile, visual communication involves lighting, the use of audio-visual devices, product placement, brand attributes, audio gimmicks such as bells, and supporting content for pre-event reminders. Each communication element is conceptually linked to the stages of AIDMA and the components of the marketing mix to create a shopping experience that is interactive, emotionally engaging, and conversion-oriented. These findings emphasize the importance of structured communication design and consumer experience-based planning in enhancing the effectiveness of live commerce.Keywords: Live Commerce, Communication Strategy, AIDMA, Marketing Mix, Shopee Live